Interlayer confinement type nickel-based catalyst as well as preparation method and application thereof

By using interlayer confined nickel-based catalysts in the ethylene polymerization reaction and using montmorillonite carriers to load NiO, the problem of decreased activity of heterogeneous nickel catalysts at high temperatures was solved, and high-activity and high-selectivity ethylene polymerization effects were achieved, simplifying the preparation process and reducing costs.

CN120618472APending Publication Date: 2025-09-12SHANGHAI ADVANCED RES INST CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510804478.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-12

Smart Images

  • Figure BDA0005452183800000091
    Figure BDA0005452183800000091
  • Figure BDA0005452183800000101
    Figure BDA0005452183800000101
  • Figure HDA0005452183810000011
    Figure HDA0005452183810000011
Patent Text Reader

Abstract

The invention provides an interlayer confinement type nickel-based catalyst as well as a preparation method and application thereof. The interlayer confinement type nickel-based catalyst comprises the following components: NiO and a carrier, the carrier is montmorillonite; the NiO is loaded on the montmorillonite. The catalyst provided by the invention has high catalytic activity and high product selectivity, and is excellent in stability. In the preparation process, no additive component or organic solvent is added, and the preparation method is simple, green and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to an interlayer confined nickel-based catalyst and a preparation method and application thereof. Background Art

[0002] Ethylene oligomerization to produce α-olefins (C4-C10) is one of the core reactions in the synthesis of high-value-added chemicals in the petrochemical industry. Its products, such as butene, hexene, and octene, serve as key raw materials for synthetic lubricant base oils, environmentally friendly plasticizers, surfactants, and high-density polyethylene comonomers, and occupy an important position in the global chemical industry chain. Unlike the traditional process of ethylene polymerization to produce high-molecular-weight polyethylene, the ethylene oligomerization reaction can achieve the selective insertion of ethylene monomers to form α-olefins of specific chain lengths through precise regulation of the active centers of the catalyst, thereby greatly improving the utilization value of the ethylene raw material. However, the reaction process involves complex chain growth and termination mechanisms, and its product distribution is extremely sensitive to the catalyst structure.

[0003] In the prior art, ethylene polymerization catalyst systems can be divided into two categories according to the form of active sites: homogeneous catalysts and heterogeneous catalysts. (1) Homogeneous catalysts: represented by Lewis acids such as AlCl3, BF3 and metallocenes, whose active center structures are uniform and whose electronic effects can be regulated by ligand modification, have good catalytic performance and industrial applications. However, they have defects such as strong corrosion to equipment, high separation energy consumption and dependence on expensive co-catalysts (such as MAO). (2) Heterogeneous catalysts: including molecular sieve catalysts, ordered mesoporous material catalysts, metal oxide catalysts and heterogeneous nickel catalysts, which have the characteristics of low cost, long life and easy product separation. Therefore, from the perspective of green chemistry, heterogeneous catalysts have greater advantages. Among them, heterogeneous nickel catalysts have become a research hotspot in recent years due to the abundant reserves of nickel and low cost.

[0004] However, heterogeneous nickel catalysts still face the following bottlenecks: 1) Selectivity defects: Some surface acidic sites on the support (such as the Lewis acid centers of Al2O3) easily trigger secondary isomerization of the product, resulting in an increased proportion of branched olefins; 2) Insufficient stability: Under high-temperature reaction conditions (>100°C), nickel nanoparticles sinter, resulting in a decrease in active site density, leading to low catalytic activity; 3) Poor process compatibility: Although some new catalysts (such as porous organic polymer-supported nickel) have increased specific surface area through supercritical CO2 activation, the preparation process is complex and involves high-pressure equipment, making industrial scale-up difficult. For example, although N-heterocyclic carbene (NHC)-coordinated nickel catalysts can achieve 88.2% C8 olefin selectivity at 80°C, they require the use of highly toxic triphenylborate as a cocatalyst; and although nickel-based molecular sieves (such as Ni-MCM-41) inhibit carbon deposition through pore confinement, their microporous structure significantly reduces the ethylene diffusion coefficient, limiting the reaction rate.

[0005] Therefore, the development of green and environmentally friendly heterogeneous Ni-based catalysts with high activity, high selectivity and stability remains a technical challenge that has not yet been overcome in this field. Summary of the Invention

[0006] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide an interlayer confined nickel-based catalyst and a preparation method and application thereof, so as to solve the problems in the prior art.

[0007] To achieve the above-mentioned purpose and other related purposes, the present invention is achieved through the following technical solutions.

[0008] A first aspect of the present invention provides an interlayer confined nickel-based catalyst, the components of the catalyst including NiO and a carrier; the carrier is montmorillonite (MMT); and the NiO is loaded on the montmorillonite.

[0009] The montmorillonite in this application is a naturally occurring clay mineral that belongs to a 2:1 type layered silicate with a flat slit structure. Its crystal structure is usually a hexagonal system, and one unit cell contains two layers of silicon-oxygen tetrahedron sheets and one layer of aluminum-oxygen octahedron sheets. The present invention uses montmorillonite (MMT) with a specific layered structure as a carrier, which is beneficial to its unique layered topological structure to provide a rigid confined microenvironment for NiO, thereby effectively inhibiting the migration and sintering of active components under high temperature reaction conditions, resulting in a decrease in catalyst activity and improving the stability of the catalyst.

[0010] The "interlayer confinement" described in the interlayer confined nickel-based catalyst in this application is precisely due to the effect brought about by the special layered structure of montmorillonite as described above. The special physical structure of montmorillonite can confine NiO particles in the interlayer, providing a rigid confined microenvironment for NiO.

[0011] At the same time, the strong metal-support interaction (SMSI) generated by this specific interlayer confinement induces the rearrangement of the NiO electron cloud density to form highly active Ni δ+ The NiO nanoparticles confined between the montmorillonite layers can synergistically optimize the reaction pathway to enhance product selectivity, resulting in a more concentrated formation of the dimerization product (butene) and reduced by-product formation.

[0012] Preferably, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 0.5 to 20 wt%, and the content of the carrier is 80 to 99.5 wt%.

[0013] Preferably, the NiO particle size is 0.5 to 30 nm, more preferably 1.0 to 27.6 nm, such as 1.2 to 2.0 nm, 1.3 to 1.8 nm, or 1.2 to 1.4 nm.

[0014] In the catalyst provided herein, the amount of loaded nickel affects the size of the NiO particles. Generally speaking, the higher the nickel content in the catalyst, the larger the NiO particle size. If the nickel content is too low, such as less than 0.5 wt%, the catalyst contains too few active components, which is not conducive to improving the catalyst's reactivity. If the nickel content is too high, such as greater than 20 wt%, the NiO particle size becomes larger, causing NiO particle agglomeration, thereby reducing the catalyst's stability and reactivity.

[0015] Preferably, the specific surface area of ​​the montmorillonite is 100 to 300 m 2 / g. More preferably, it is 150 to 300 m 2 / g. For example, it can be 158~293m 2 / g, 158~257m 2 / g, 257~293m 2 / g, and most preferably 290 to 300 m 2 If the specific surface area of ​​montmorillonite is too large, the carrier's adsorption performance may be too strong, the mass transfer resistance may increase, and the catalyst activity and reaction rate may be affected; if the specific surface area of ​​montmorillonite is too small, the active components may not be evenly dispersed, affecting the catalyst activity and stability.

[0016] Preferably, the montmorillonite has a cation exchange capacity of 70 to 140 mmol / g. More preferably, it is 90 to 140 mmol / g. For example, it may be 90 to 120 mmol / g, 120 to 140 mmol / g, and most preferably 130 to 140 mmol / g. If the cation exchange capacity of the montmorillonite is too high, such as exceeding 140 mmol / g, the crystal structure may become unstable, reducing catalyst stability. If the cation exchange capacity of the montmorillonite is too low, the number of active sites provided may be limited, failing to meet reaction requirements, resulting in reduced catalytic activity.

[0017] Preferably, the pore size of the montmorillonite is 2 to 50 nm, more preferably 2 to 10 nm, such as 4.78 to 5.89 nm, 4.78 to 4.85 nm, 4.85 to 5.89 nm, and most preferably 4.8 to 5.5 nm.

[0018] Preferably, the montmorillonite includes one or more of Yixian montmorillonite, Huangyue montmorillonite and Anji montmorillonite.

[0019] The physical structural parameters of the montmorillonite carrier in this application are very important parameters. Only within the above ranges can the technical effects described in this application be achieved.

[0020] The second aspect of the present invention provides a method for preparing the interlayer confined nickel-based catalyst as described above, comprising the following steps: providing a metal salt solution containing the nickel element and the montmorillonite; mixing the metal salt solution with the montmorillonite so that the solute in the metal salt solution is completely loaded on the montmorillonite, removing the solvent to obtain a solid; and drying and calcining the solid to obtain the interlayer confined nickel-based catalyst.

[0021] Preferably, the montmorillonite is pre-treated by drying before mixing.

[0022] Preferably, the loading is performed by an impregnation method or an ion exchange method.

[0023] Preferably, the drying temperature is 60-150° C., and the drying time is 6-24 hours.

[0024] Preferably, the calcination temperature is 400-600° C., and the calcination time is 2-10 hours. For example, the calcination temperature can be 400-550° C., 550-600° C., and the calcination time can be 2-5 hours, 5-10 hours.

[0025] Preferably, the calcination is carried out in one or both of nitrogen and argon gases.

[0026] Preferably, the drying pretreatment temperature is 60-150° C., and the drying pretreatment time is 6-12 hours. For example, the drying pretreatment temperature can be 60-80° C., 80-150° C., and the drying pretreatment time can be 6-8 hours, or 8-12 hours.

[0027] Preferably, when the impregnation method is adopted, the impregnation is continued until the carrier montmorillonite reaches saturated water absorption.

[0028] Preferably, the ion exchange temperature is 40 to 80° C., and the ion exchange time is 6 to 24 hours.

[0029] Preferably, after removing the solvent, washing is performed. More preferably, deionized water is used for the washing.

[0030] A third aspect of the present invention provides a use of the above-mentioned interlayer confined nickel-based catalyst in ethylene oligomerization reaction.

[0031] Preferably, the major product of the ethylene oligomerization reaction comprises a dimer product.

[0032] Preferably, the reaction device for the ethylene oligomerization reaction is a fixed bed reactor.

[0033] A fourth aspect of the present invention provides a method for ethylene oligomerization, using the interlayer confined nickel-based catalyst described above.

[0034] Preferably, the conditions for the ethylene oligomerization reaction include one or more of the following features:

[0035] The reaction temperature is 80-300°C;

[0036] The reaction pressure is 0.1~4MPa;

[0037] Reaction space velocity is 500~10000h -1 .

[0038] For example, the reaction temperature can be 80-250°C, 250-300°C; the reaction pressure can be 0.1-2 MPa, 2-4 MPa; the reaction space velocity can be 500-2000 h -1 2000~10000h -1 .

[0039] Preferably, the product of the ethylene oligomerization reaction comprises a dimer product.

[0040] Preferably, the reaction device for the ethylene oligomerization reaction is a fixed bed reactor.

[0041] Beneficial effects:

[0042] 1) The catalyst provided by the present invention has a specific interlayer confined structure, which can be used as a nanoreactor to achieve efficient enrichment and diffusion of ethylene gas, so that it exhibits higher catalytic activity and higher C4 olefin (butene) selectivity in the reaction of using ethylene gas as a catalyst to synthesize small molecule basic raw materials α-olefins.

[0043] 2) The catalyst provided by the present invention can avoid the decrease in active site density caused by the migration and sintering of nickel elements under high-temperature reaction conditions, thereby avoiding the decrease in catalytic activity of the catalyst; it has good stability and can maintain its activity relatively stable after 50 hours of continuous reaction, maintaining at 90% of the original activity without any decrease.

[0044] 3) The active ingredient in the technical solution of the present invention is metallic nickel, which is abundant in reserves and low in cost. At the same time, the preparation method in this application is simple and easy to operate. The catalyst with a specific interlayer confined structure in this application can be obtained only by aqueous impregnation or ion exchange, combined with drying and calcination. The use of organic / toxic solvents, expensive / toxic co-catalysts, etc. is avoided in the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1Shown is a transmission electron microscope image of the interlayer confined nickel-based catalyst prepared in Example 1 of the present invention.

[0046] Figure 2 Shown are the XRD test results of the interlayer confined nickel-based catalysts prepared in Examples 1 to 3 of the present invention.

[0047] Figure 3 Shown is a graph showing the stability analysis results of the interlayer confined nickel-based catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0048] The following describes the implementation of the present invention through specific embodiments. People skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0049] Before further describing the specific embodiments of the present invention, it should be understood that the scope of the present invention is not limited to the specific embodiments described below. It should also be understood that the terminology used in the examples is intended to describe specific embodiments and is not intended to limit the scope of the present invention. The experimental procedures in the following examples, where specific conditions are not specified, were generally performed under conventional conditions or according to the conditions recommended by the respective manufacturers.

[0050] When the embodiments provide numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the understanding of the prior art by those skilled in the art and the description of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention may also be used to implement the present invention.

[0051] The technical solution of this application utilizes a heterogeneous catalyst, which is more environmentally friendly, less expensive, and easier to separate the product from the catalyst than homogeneous catalysts. Compared to heterogeneous catalysts in the prior art, this catalyst utilizes a montmorillonite carrier with a specific structure combined with a specific nickel content, enabling highly uniform dispersion of NiO particles within the carrier. This prevents NiO particle migration and clustering, resulting in excellent catalyst stability and avoiding the problem of catalyst deactivation during high-temperature reactions.

[0052] The catalyst composition of the technical solution of this application only contains a montmorillonite carrier and metallic nickel, and does not use any co-catalysts (such as methylaluminoxane, trimethylaluminum, triethylaluminum, modified methylaluminoxane, etc.) or organic solvents, thereby avoiding the problems of catalyst decomposition, deactivation, poor stability, and poor product selectivity caused by the presence of multiple active ingredients. At the same time, the use of co-catalysts and organic solvents also increases the cost of catalyst preparation, increases the requirements for equipment used, makes the instruments used expensive, and causes pollution during the preparation process.

[0053] In the following examples of this application, the specific surface area of ​​the Yixian montmorillonite used is 293m 2 / g, cation exchange capacity is 140mmol / g, pore size is 4.85nm; the specific surface area of ​​Anji montmorillonite is 158m 2 / g, cation exchange capacity is 90mmol / g, pore size is 5.89nm; the specific surface area of ​​Huangyue montmorillonite is 257m 2 / g, a cation exchange capacity of 120 mmol / g, and a pore size of 4.78 nm. The pore size distributions of activated carbon (AC), SiO2, and Al2O3 used in the comparative example are comparable to the physical parameters of the above-mentioned montmorillonite.

[0054] The specific surface area and pore size were measured using a Micromeritics TriStar 3020 physical adsorption analyzer, where the specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method.

[0055] The pore size distribution was analyzed based on the Barrett-Joyner-Halenda (BJH) model.

[0056] The cation exchange capacity was tested by standard ammonium acetate exchange combined with inductively coupled plasma spectrometry: first, the sample was saturated with 1 mol / L neutral ammonium acetate solution for three times, and then the characteristic cations (Na + , K + , Ca 2+ Mg 2+ The total content of the sample (e.g., cation exchange capacity) was finally calculated.

[0057] Example 1

[0058] This embodiment provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0059] 1) 19.8 g of Yixian montmorillonite was pretreated by drying in an oven at 80°C for 8 h to completely remove moisture from the montmorillonite.

[0060] 2) Dissolve 0.99 g of Ni(NO3)2·6H2O in deionized water, stirring or ultrasonicating until completely dissolved to obtain a metal salt solution; completely immerse the pretreated montmorillonite in the metal salt solution until the montmorillonite carrier reaches saturation and no longer absorbs water, so that the solute fully enters the interlayer structure of the MMT;

[0061] 3) After the impregnation is completed, place the mixture in a fume hood at 25° C. for 24 hours to remove excess solvent and obtain a solid;

[0062] 4) The solid obtained in step 3) was placed in an oven, dried at 60° C. for 24 h, and then placed in a tubular furnace and calcined at 550° C. for 5 h under nitrogen to obtain the interlayer confined nickel-based catalyst.

[0063] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 1 wt %, the content of the montmorillonite is 99 wt %, and the particle size of NiO is 1.3 nm.

[0064] Example 2

[0065] This embodiment provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0066] 1) Same as Example 1;

[0067] 2) Except for taking 0.495g of Ni(NO3)2·6H2O, the rest is the same as Example 1;

[0068] 3) Same as Example 1;

[0069] 4) Same as Example 1.

[0070] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 0.5 wt %, the content of the montmorillonite is 99.5 wt %, and the particle size of NiO is 1.0 nm.

[0071] Example 3

[0072] This embodiment provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0073] 1) Same as Example 1;

[0074] 2) Except for taking 5.16g of Ni(NO3)2·6H2O, the rest is the same as Example 1;

[0075] 3) Same as Example 1;

[0076] 4) Same as Example 1.

[0077] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 5wt%, the content of the montmorillonite is 99.5wt%, and the particle size of NiO is 17.2nm.

[0078] Example 4

[0079] This embodiment provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0080] 1) Except for taking 9.9g of Yixian montmorillonite, the rest is the same as in Example 1;

[0081] 2) Except for taking 5.45g of Ni(NO3)2·6H2O, the rest is the same as Example 1;

[0082] 3) Same as Example 1;

[0083] 4) Same as Example 1.

[0084] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 10 wt %, the content of the montmorillonite is 90 wt %, and the particle size of NiO is 21.4 nm.

[0085] Example 5

[0086] This embodiment provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0087] 1) Except for taking 9.9g of Yixian montmorillonite, the rest is the same as in Example 1;

[0088] 2) Except for taking 12.26g of Ni(NO3)2·6H2O, the rest is the same as Example 1;

[0089] 3) Same as Example 1;

[0090] 4) Same as Example 1.

[0091] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 20 wt %, the content of the montmorillonite is 80 wt %, and the particle size of NiO is 27.6 nm.

[0092] Example 6

[0093] 1) Same as Example 1;

[0094] 2) Except for taking 0.81g of NiCl2·6H2O, the rest is the same as Example 1;

[0095] 3) Same as Example 1;

[0096] 4) Same as Example 1.

[0097] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 1 wt %, the content of the montmorillonite is 99 wt %, and the particle size of NiO is 1.7 nm.

[0098] Example 7

[0099] This embodiment provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0100] 1) Except for taking 19.8g of Anji montmorillonite, the rest is the same as in Example 1;

[0101] 2) Same as Example 1;

[0102] 3) Same as Example 1;

[0103] 4) Same as Example 1.

[0104] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 1 wt %, the content of the montmorillonite is 99 wt %, and the particle size of NiO is 1.8 nm.

[0105] Example 8

[0106] This embodiment provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0107] 1) Except for taking 19.8g of Huangyue montmorillonite, the rest is the same as in Example 1;

[0108] 2) Same as Example 1;

[0109] 3) Same as Example 1;

[0110] 4) Same as Example 1.

[0111] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 1 wt %, the content of the montmorillonite is 99 wt %, and the particle size of NiO is 1.5 nm.

[0112] Comparative Example 1

[0113] This comparative example provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0114] 1) Same as Example 1;

[0115] 2) Except for taking 0.197g of Ni(NO3)2·6H2O, the rest is the same as Example 1;

[0116] 3) Same as Example 1;

[0117] 4) Same as Example 1.

[0118] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 0.2 wt %, the content of the montmorillonite is 99.8 wt %, and the particle size of NiO is 0.8 nm.

[0119] Comparative Example 2

[0120] This comparative example provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0121] 1) Same as Example 1;

[0122] 2) Except for taking 32.7g of Ni(NO3)2·6H2O, the rest is the same as Example 1;

[0123] 3) Same as Example 1;

[0124] 4) Same as Example 1.

[0125] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 25 wt %, the content of the montmorillonite is 75 wt %, and the particle size of NiO is 31.2 nm.

[0126] Comparative Example 3

[0127] This comparative example provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0128] 1) Except for taking 19.8 g of activated carbon (AC), the rest is the same as Example 1;

[0129] 2) Same as Example 1;

[0130] 3) Same as Example 1;

[0131] 4) Same as Example 1.

[0132] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 1 wt %, the content of the activated carbon (AC) is 99 wt %, and the particle size of NiO is 1.4 nm.

[0133] Comparative Example 4

[0134] This comparative example provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0135] 1) Except for taking 19.8g SiO2, the rest is the same as Example 1;

[0136] 2) Same as Example 1;

[0137] 3) Same as Example 1;

[0138] 4) Same as Example 1.

[0139] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 1wt%, the content of the SiO2 is 99wt%, and the particle size of NiO is 1.6nm.

[0140] Comparative Example 5

[0141] This comparative example provides a specific interlayer confined nickel-based catalyst, comprising the following steps:

[0142] 1) Except for taking 19.8g of Al2O3, the rest is the same as Example 1;

[0143] 2) Same as Example 1;

[0144] 3) Same as Example 1;

[0145] 4) Same as Example 1.

[0146] Wherein, based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 1wt%, the content of the Al2O3 is 99wt%, and the particle size of NiO is 2.0nm.

[0147] Application Examples

[0148] 1.0 g of the catalysts prepared in Examples 1 to 8 and Comparative Examples 1 to 5 were weighed and mixed with 3.0 g of quartz sand of the same mesh size to ensure uniform distribution of the catalyst during the reaction. The catalysts were then used in the ethylene oligomerization reaction to prepare α-olefins. The total product was measured for 24 hours for component analysis. The reaction apparatus was a fixed-bed reactor. The specific steps of the reaction were as follows: before the reaction began, the reaction system was back-pressurized and heated with pure nitrogen until the reaction temperature reached 250°C and the pressure reached 2 MPa. The gas was then switched to pure C2H4 reaction gas and heated for 2000 h. -1 After the reaction, the types and contents of the various components contained in the products of the various examples and comparative examples were analyzed using a gas chromatograph Agilent 7890B, and the catalytic activity of the reaction catalyst and the selectivity of the product were calculated accordingly.

[0149] The reaction results are shown in Table 1.

[0150] Table 1

[0151]

[0152]

[0153] The catalytic activity (mol / gNi / h) in this table refers to the total number of moles of ethylene dimerization products and trimerization products generated by the reaction of unit mass of Ni element per unit time.

[0154] The NiO particle size was tested by using a FEI Tecnai G2 F20 S-TWIN transmission electron microscope (TEM) and high-resolution transmission electron microscope (HRTEM) at an accelerating voltage of 200 kV. The particle size was then statistically analyzed using measurement software and the average value was calculated.

[0155] As can be seen from Table 1, compared with the comparative example, the interlayer confined nickel-based catalyst prepared in the embodiment of the present application not only has high catalytic activity, which can be as high as 96.4 mol / gNi / h, but also can maintain high selectivity for dimerization products, making the selected products almost specific.

[0156] It can be seen from Examples 1 to 5 that the amount of nickel loaded in the catalyst has an impact on the NiO particle size. Generally speaking, the more nickel loaded in the catalyst, the larger the NiO particle size. The particle size of NiO described in the Examples and Comparative Examples of the present application is the average particle size of NiO. It should be noted that although the content of nickel loaded in the catalyst will affect the particle size of NiO, the two are not strictly one-to-one corresponding. Using different carriers or raw materials will produce differences within a certain range. For example, in Examples 1 to 5 of the present application, when the content of nickel in the catalyst is wt%, the particle size of NiO is 1.3 to 2.0 nm.

[0157] Furthermore, Examples 1 to 5 show that the catalyst's catalytic activity is highest when the nickel content is 1 wt%. That is, when the nickel content is less than 1 wt%, the catalyst's activity increases with increasing nickel content, while when the nickel content is greater than 1 wt%, the catalyst's activity decreases with increasing nickel content. This may be because, within a certain range of 1 wt%, as the loaded nickel content increases, the number of active sites in the catalyst increases, leading to increased reaction activity. When the loaded nickel content exceeds 1 wt%, the NiO particle size also increases with the loading, and this increased NiO particle size leads to agglomeration of the NiO particles, resulting in decreased catalyst stability and decreased reaction activity.

[0158] It can be seen from Examples 1 and 6 that the types of salt solutions providing nickel elements can be varied, and the reaction activity and high dimerization product selectivity of the catalyst are independent of the types of salt solutions providing nickel elements.

[0159] From Examples 1 and 7-8, it can be seen that the type of MMT carrier also affects the effect of the catalyst. When Yixian montmorillonite is used, the catalytic activity and product selectivity of the catalyst are the best.

[0160] It can be seen from the examples and comparative examples 1-2 that the nickel content is a very important parameter. If the nickel content is too low, the catalytic activity of the catalyst is low; if the nickel content is too high, the catalytic activity of the catalyst will also be reduced.

[0161] It can be seen from the examples and comparative examples 3 to 5 that the choice of carrier is very specific. Only by selecting a montmorillonite carrier with a specific structure as described in this application can the technical effect of both high reaction activity and high product selectivity in this application be achieved.

[0162] The applicant also used a JEOL-JEM 2011 microscope operated at 200kV to observe the structure of the interlayer confined nickel-based catalyst prepared in Example 1. The specific results are shown in Figure 1 .

[0163] Depend on Figure 1 It can be seen that the white spherical particles are NiO particles (see Figure 1 (circled) It can be seen that in the catalyst prepared in Example 1, NiO particles are uniformly dispersed in the form of nanoclusters between the layers of montmorillonite nanosheets. This indicates that the NiO particles in the catalyst are evenly distributed in the carrier, without any particle migration or aggregation.

[0164] This uniform dispersion property is due to the unique layered structure of montmorillonite, whose interlayer domains provide ideal spatial constraints for the confined growth of NiO, thereby effectively inhibiting the migration and aggregation of metal particles.

[0165] The applicant also conducted XRD tests on the interlayer confined nickel-based catalysts with different loadings prepared in Examples 1 to 3 of the present application. The specific results are shown in Figure 2 .

[0166] Depend on Figure 2 It can be seen that Examples 1 to 3 all retain the complete characteristic diffraction peaks of montmorillonite (see Figure 2 The diamond mark indicates that the introduction of nickel does not destroy the original layered skeleton structure of montmorillonite. In addition, as the nickel content increases, the characteristic diffraction peaks attributed to NiO or metallic Ni are gradually detected in the XRD spectrum (see Figure 2In the case of low nickel content, such as in Examples 1 and 2, XRD experiments did not detect characteristic diffraction peaks attributable to NiO or metallic Ni. This indicates that in the catalyst prepared by the technical solution of the present application, the nickel element is highly dispersed in the montmorillonite.

[0167] In summary, the NiO in the catalyst prepared by the technical solution of the present application is highly uniformly dispersed in the interlayer of the montmorillonite nanosheets in the form of nanoclusters, without migration and agglomeration.

[0168] The applicant also conducted a stability test on the interlayer confined nickel-based catalyst prepared in Example 1 of the present application. The specific test method is: weigh 1.0g of the catalyst in Example 1 and mix it thoroughly with 3.0g of fine quartz sand, and then place it in a fixed bed reactor. At the beginning of the experiment, the system was back-pressured to 2MPa under nitrogen conditions and slowly heated to a reaction temperature of 220°C. After the system temperature reached 220°C, the nitrogen flow was cut off and an ethylene flow was introduced as a reaction raw material with an air velocity of 1800mL / g / h. The catalyst was evaluated for stability under an ethylene atmosphere for 50h. The specific implementation results are shown in FIG. Figure 3 .

[0169] Depend on Figure 3 It can be seen that the catalyst prepared in Example 1 can work continuously for 50 hours and still maintain its catalytic activity above 90%, indicating that the catalyst has excellent stability and can achieve high-activity continuous catalysis without deactivation.

[0170] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. An interlayer confined nickel-based catalyst, characterized in that: The components of the catalyst include NiO and a carrier; the carrier is montmorillonite; and the NiO is loaded on the montmorillonite.

2. The catalyst according to claim 1, characterized in that Based on the total mass of the nickel element and the carrier in the catalyst, the content of the nickel element is 0.5-20wt%, and the content of the carrier is 80-99.5wt%.

3. The catalyst according to claim 1, characterized in that The specific surface area of ​​the montmorillonite is 100 to 300 m 2 / g; and / or, the cation exchange capacity of the montmorillonite is 70 to 140 mmol / g; And / or, the pore size of the montmorillonite is 2 to 50 nm.

4. A method for preparing an interlayer confined nickel-based catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: A metal salt solution containing the nickel element and the montmorillonite are provided; the metal salt solution and the montmorillonite are mixed so that the solute in the metal salt solution is completely loaded on the montmorillonite, and the solvent is removed to obtain a solid; the solid is dried and then calcined to obtain the interlayer confined nickel-based catalyst.

5. The preparation method according to claim 4, characterized in that The montmorillonite needs to be dried before mixing; and / or, the loading is performed by an impregnation method or an ion exchange method; and / or, the drying temperature is 60 to 150° C.; and / or, the calcination temperature is 400-600° C.; And / or, the calcination is performed in one or both of nitrogen and argon gases.

6. The preparation method according to claim 5, characterized in that When the impregnation method is adopted, until the carrier montmorillonite reaches saturated water absorption; And / or, the ion exchange temperature is 40 to 80° C.; and the ion exchange time is 6 to 24 hours.

7. Use of the interlayer confined nickel-based catalyst according to any one of claims 1 to 3 in ethylene oligomerization.

8. A method for ethylene oligomerization, characterized in that: The interlayer confined nickel-based catalyst as described above is used.

9. The method according to claim 8, characterized in that The conditions for the ethylene oligomerization reaction include one or more of the following characteristics: The reaction temperature is 80-300°C; The reaction pressure is 0.1~4MPa; Reaction space velocity is 500~10000h -1 .

10. The method according to claim 8, characterized in that The product of the ethylene oligomerization reaction includes a dimer product; And / or, the reaction device for the ethylene oligomerization reaction is a fixed bed reactor.